Postawy konsumentów wobec żywności ekologicznej - Pilarski, Stanisław (Consumer Attitudes Towards Organic Food, 2005)
The aim of the paper is to determine the level and structure of organic food consumption. It was observed that the consumption of this food in Poland is not high yet, even among the consumers of a very high social status. The consumers appreciate this food because of its healthy and nourishing values, which are related to their personal not social benefits. The availability of organic animal products is significantly limited by poor distribution and limited range.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 192-199